Complex-Type N-Glycans Influence the Root Hair Landscape of Arabidopsis Seedlings by Altering the Auxin Output - Frank, Manuel; Kaulfürst-Soboll, Heidi; Fischer, Kerstin; von Schaewen, Antje (Frontiers in Plant Science, 2021)
Roots supply plants with nutrients and water, besides anchoring them in the soil. The primary root with its lateral roots constitutes the central skeleton of the root system. In particular, root hairs increase the root surface, which is critical for optimizing uptake efficiency. During root-cell growth and development, many proteins that are components of e.g. the cell wall and plasma membrane are constitutively transported through the secretory system and become posttranslationally modified. Here, the best studied posttranslational modification is protein N-glycosylation. While alterations in the attachment/modification of N-glycans within the ER lumen results in severe developmental defects, the impact of Golgi-localized complex N-glycan modification, particularly on root development, has not been studied in detail. We report that impairment of complex-type N-glycosylation results in a differential response to synthetic phytohormones with earlier and increased root-hair elongation. Application of either the cytokinin BAP, the auxin NAA, or the ethylene precursor ACC revealed an interaction of auxin with complex N-glycosylation during root-hair development. Especially in gntI mutant seedlings, the early block of complex N-glycan formation resulted in an increased auxin sensitivity. RNA-seq experiments suggest that gntI roots have permanently elevated nutrient-, hypoxia- and defense-stress responses, which might be a consequence of the altered auxin responsiveness.